Frying practices, oils quality and development of natural adsorbents to regenerate frying oils used by unlicensed street vendors of fried meat in Bamenda, North-West Cameron - Gires Boungo Teboukeu; Aphrodite Tchewonpi Choumessi; Audrey Akaanie Andongatei; Fabrice Tonfack Djikeng; Ronice Zokou; Clifford Boubga; Lifoter Kenneth Navti (Food Chemistry Advances)
This study aimed at assessing the frying practices, oils quality used by street vendors of fried meat in Bamenda and also develop natural absorbents to regenerate oils after frying. 31 vendors were interviewed on frying practices. Sample oils collected were analyzed measuring oxidation parameters. 10 % of each activated adsorbent prepared from groundnut shells and rice husks was mixed with degraded oils and the oxidation parameters before and after adsorption were evaluated. Results showed that none of the vendors followed the standard number of 08 frying cycles. Also, 54.84 % of the oils used for frying were dark and the filtration methods of the oils used after frying do not adsorb and remove oxidation products. Analysis of all oil samples showed extremely high levels of degradation with aldehydes up to 3–4 times higher than the standard in most samples. The treatment of degraded oils, regardless of the activated adsorbent used, reduced the free fatty acids, primary (peroxides) and secondary (aldehydes) oxidation products in the oils. The percentage improvement in oil quality was highest for the anisidine value (31.24 to 58.91 %) showing that the adsorbents adsorb/remove more aldehydes. The use of these adsorbents by street vendors for oil regeneration should be recommended.